تقييم أنسب نظام لدرجات شراء التبوغ الشرقية العراقية - رسول, عبدالسلام عبدالرحمن (Sulaimani Journal for Pure and Applied Sciences, 2002)
In this study, the current conditions of cured tobacco quality received from the local tobacco farmers have been studied and it has been proved that they were of low standard according to ashes, nicotine and schmuk number percentage, as well as being of middle / bad qualities. (A penta grading) system has failed in the unified classes rates A, B and C resulting from hand process of manipulate classes by using Chi-squire correspondence test were dissimilar comparing to the unified classes rates A, B and C expected to be produced. The instability in purchase rates indicates that the (tri-gradation) system is the most suitable, since it includes the currently available tobacco sorts in the region. This system depends on the merging of the excellent and the first classes and exchanging it with the first class only and merging the second and the third classes and exchanging them with the second class only, as well as changing the fourth class nomination to the third class.
Keywords: Tobacco commercial grades